PENGEMBANGAN LKS BERBASIS PENDEKATAN INKUIRI TERBIMBING DALAM PEMBELAJARAN EKONOMI - Made Desi Setianingsih; Erlina Rupaidah; Edy Purnomo (FKIP Unila, 2016)
This research aimed to develop students' worksheet of guided inquiry -based approach to the matter of economic activities of producers and consumers . The method used was research and development (RD) with ASSURE development model. Based on the results of research, it can conclude that: (1) the design and syntax of LKS based economy guided inquiry is using a 6 -step model of ASSURE as follows : analyze the learner, state the objective, select the method, combine the media and learning materials, utilize the materials, require the learner participation, evaluate and revise, (2) testing the effectiveness of economic students' worksheet based guided inquiry , the average learning outcomes in the experiment class which study using economic worksheets development is higher than the average learning outcomes of control class which is not using the product development results. Students' worksheet based guided inquiry approach of economy can be said that it is effective and fit to use.Penelitian ini bertujuan untuk mengembangkan LKS berbasis pendekatan inkuiri terbimbing pada materi kegiatan ekonomi produsen dan konsumen. Metode penelitian yang digunakan ialah penelitian dan pengembangan (RD) dengan model pengembangan ASSURE. Berdasarkan hasil penelitian dapat disimpulkan: (1) desain dan sintak LKS ekonomi berbasis inkuiri terbimbing yaitu menggunakan 6 langkah model Assure sebagai berikut: menganalisis pembelajar, tujuan pembuatan LKS, memilih materi, memadukan materi dan media, libatkan partisipasi siswa, evaluasi dan revisi, (2) pengujian efektifitas LKS ekonomi, rata-rata hasil belajar pada kelas eksperimen yang belajar dengan menggunakan pengembangan LKS ekonomi lebih tinggi dari rata-rata hasil belajar kelas kontrol yang belajar dengan tidak menggunakan produk hasil pengembangan. Maka LKS ekonomi berbasis pendekatan inkuiri terbimbing dapat dikatakan efektif dan layak digunakan.Kata kunci: LKS, pendekatan inkuiri terbimbing, hasil belajar